THE ROLE OF NATIONAL VALUES AND SPIRITUAL AND EDUCATIONAL WORKS IN THE EDUCATION OF THE YOUNG GENERATION - Mavlanova Mehnbonu Obid qizi; Koryogdiyev Zufar Okhunjonovich (Journals Park Publishing, 2023)
In the article, the role of child education in society. The work being carried out on the education of young people, including the essence of Resolution 5040, adopted by President Sh. Mirziyoyev, was shown.
Keywords: education, ritual, material wealth, tradition, spiritual-educational reforms, value, behavior, national pride, ideology.